The Nedd8‐activating enzyme inhibitor MLN4924 (TAK‐924/Pevonedistat) induces apoptosis via c‐Myc‐Noxa axis in head and neck squamous cell carcinoma. (19th October 2018) - Zhang, Wenjuan; Liang, Yupei; Li, Lihui; Wang, Xiaofang; Yan, Zi; Dong, Changsheng; Zeng, Mu‐Sheng; Zhong, Qian; Liu, Xue‐Kui; Yu, Jinha; Sun, Shuyang; Liu, Xiaojun; et al.
Abstract: Objectives: The present study aimed to reveal expression status of the neddylation enzymes in HNSCC and to elucidate the anticancer efficacy and the underlying mechanisms of inhibiting neddylation pathway. Materials and methods: The expression levels of neddylation enzymes were estimated by Western blotting in human HNSCC specimens and bioinformatics analysis of the cancer genome atlas (TCGA) database. Cell apoptosis was evaluated by Annexin V fluorescein isothiocyanate/propidium iodide (Annexin V‐FITC/PI) stain and fluorescence‐activated cell sorting (FACS). Small interfering RNA (siRNA) and the CRISPR‐Cas9 system were used to elucidate the underlying molecular mechanism of MLN4924‐induced HNSCC apoptosis. Results: Expression levels of NAE1 and UBC12 were prominently higher in HNSCC tissues than that in normal tissues. Inactivation of the neddylation pathway significantly inhibited malignant phenotypes of HNSCC cells. Mechanistic studies revealed that MLN4924 induced the accumulation of CRL ligase substrate c‐Myc that transcriptionally activated pro‐apoptotic protein Noxa, which triggered apoptosis in HNSCC. Conclusions: These findings determined the over‐expression levels of neddylation enzymes in HNSCC and revealed novel mechanisms underlying neddylation inhibition induced growth suppression in HNSCC cells, which provided preclinical evidence for further clinical evaluation of neddylation inhibitors (eg, MLN4924) for the treatment of HNSCC.